Four facets of cultural intelligence predictors of knowledge sharing intentions - Messarra, Leila (2008)
The purpose of this study was to investigate whether the four facets of cultural intelligence correlates with the intention to share knowledge. The sample consisted of 164 employees working in multinational organizations. Results indicate that metacognitive, motivational, and behavioral cultural quotients (CQ) are predictors of knowledge sharing intentions. No relation was found between cognitive CQ and knowledge sharing intentions.